Depletion of Limiting rDNA Structural Complexes Triggers Chromosomal Instability and Replicative Aging of Saccharomyces cerevisiae. Issue 1 (6th March 2019) - Fine, Ryan D; Maqani, Nazif; Li, Mingguang; Franck, Elizabeth; Smith, Jeffrey S
Abstract: Sir2 is a highly conserved NAD + -dependent histone deacetylase that functions in heterochromatin formation and promotes replicative life span (RLS) in the budding yeast, Saccharomyces cerevisiae . Within the yeast rDNA locus, Sir2 is required for efficient cohesin recruitment and maintaining the stability of the tandem array. In addition to the previously reported depletion of Sir2 in replicatively aged cells, we discovered that subunits of the Sir2 -containing complexes silent information regulator (SIR) and regulator of nucleolar silencing and telophase (RENT) were depleted. Several other rDNA structural protein complexes also exhibited age-related depletion, most notably the cohesin complex. We hypothesized that mitotic chromosome instability (CIN) due to cohesin depletion could be a driver of replicative aging. Chromatin immunoprecipitation assays of the residual cohesin (Mcd1 -Myc) in moderately aged cells showed strong depletion from the rDNA and initial redistribution to the point centromeres, which was then lost in older cells. Despite the shift in cohesin distribution, sister chromatid cohesion was partially attenuated in aged cells and the frequency of chromosome loss was increased. This age-induced CIN was exacerbated in strains lacking Sir2 and its paralog, Hst1, but suppressed in strains that stabilize the rDNA array due to deletion of FOB1 or through caloric restriction. Furthermore, ectopic expression of MCD1 from a doxycycline-inducible promoter was sufficient to suppress rDNA instability in aged cells and to extend RLS. Taken together, we conclude that age-induced depletion of cohesin and multiple other nucleolar chromatin factors destabilize the rDNA locus, which then results in general CIN and aneuploidy that shortens RLS.